2022
DOI: 10.1038/s42003-022-03451-4
|View full text |Cite
|
Sign up to set email alerts
|

Proline utilization A controls bacterial pathogenicity by sensing its substrate and cofactors

Abstract: Previous reports indicate that proline utilization A (PutA) is involved in the oxidation of proline to glutamate in many bacteria. We demonstrate here that in addition to its role in proline catabolism, PutA acts as a global regulator to control the important biological functions and virulence of Ralstonia solanacearum. PutA regulates target gene expression levels by directly binding to promoter DNA, and its regulatory activity is enhanced by L-proline. Intriguingly, we reveal that the cofactors NAD+ and FAD b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Song et al (79) argued that this signaling system might be a new type of cell-cell communication in RSSC. Similar modulators regulated by amino acids and related substances have recently been reported (15,99). These studies also mentioned the possibility that the systems are new cell-cell communications.…”
Section: Other Cell-cell Communicationsupporting
confidence: 74%
See 1 more Smart Citation
“…Song et al (79) argued that this signaling system might be a new type of cell-cell communication in RSSC. Similar modulators regulated by amino acids and related substances have recently been reported (15,99). These studies also mentioned the possibility that the systems are new cell-cell communications.…”
Section: Other Cell-cell Communicationsupporting
confidence: 74%
“…Extracellular 3-OH MAME levels were significantly reduced in epsB and lecM (35,36). In recent years, lack of adequate resources has been demonstrated to suppress the activation of the QS circuit (15,79,99). Therefore, there must be avoidance systems to suppress the production of high-energy-requiring virulence factors in inappropriate cellular states.…”
Section: Feedback Regulation Of the Phc Quorum-sensing Systemmentioning
confidence: 99%
“…Alternatively, DC3000 PutA possesses a predicted DNA-binding domain that may directly or indirectly regulate the expression of T3SS-encoding genes. In support of this possibility, PutA in the plant pathogen Ralstonia solanacearum directly binds to the promoter of virulence-associated gene epsA and upregulates epsA expression in a proline-dependent manner 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been reported that the T3E RipI interacts with plant glutamate decarboxylases to alter plant metabolism and support bacterial growth (137), thus revealing a link between a T3E and the directed biosynthesis of nutrients by the pathogen once inside its host. Third, it became increasingly clear that the metabolic potential of R. solanacearum is controlled by key virulence regulators and that this regulation plays a crucial role in the plant, probably at several stages of the infection process (47,61,94,96,98,144).…”
Section: Nutritional Virulencementioning
confidence: 99%